QUANTITATIVE STUDY OF TAXPAYER COMPLIANCE IN JAKARTA - Aan Amalia (Universitas Pamulang, 2022)
Taxes are the main source of income and are the driving force for development, so the central and local governments need to take real action in increasing public awareness in paying taxes. This research actually wants to see and analyze how the determining factors in creating awareness of paying taxes, including the motivation to pay taxes, tax services organized by the government, sanctions and the ability to pay taxes. In the proof, this research uses quantitative method with path regression analysis. The research was conducted at Jakarta tax office with a total of 100 respondents. Respondents in this study were Jakartans who were registered as taxpayers in South Jakarta. In taking the sample, a simple random technique was used, namely taxpayers who were willing to fill out a questionnaire. In the results of the study, it can be seen that, either in partial or joint models, there is a strong relationship between motivation, sanctions, economic/financial conditions of taxpayers, tax services and awareness of paying taxes. However, the most dominant thing from all models is that people will be more aware of paying taxes if there are sanctions in the form of administrative fines.Keywords: Tax Awareness, Tax Obedience, The Spirit of Paying Taxes, Financial Condition, Tax Services